PENCITRAAN PEREMPUAN PASCA PERCERAIAN DALAM PERSPEKTIF GENDER - Imron, Ahmad Ali (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
Realities of gender inequality often happened in our society life. These are not thought as a problem because of unawareness and insensitivity of it. One of them is stereotype or negative stigma to widow’s status. This is formed by social and cultural construction. Public views of widow’s image can be analyzed through social and culture as well as concept of gender perspective. Actually most of divorce cases, woman (wife) has more negative impact than a man side. Widow is also identical as second social status. In other gender inequalities, stereotype of widow and widower can be also analyzed if women have function as leader of a family. In fact, they are never categorized as a priority group in development context; the subject as a leader of family is measured by masculinity. It proves that domination of patriarchy culture still influence in many sectors.